พฤติกรรมการใช้บริการการท่องเที่ยวของนักท่องเที่ยวชาวตะวันออกกลางในเขต กรุงเทพมหานคร - ยะดี และคณะ, ดาลีซะห์ (วารสารวิชาการการท่องเที่ยวไทยนานาชาติ, 2015)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์ 3 ประการ คือ 1) เพื่อศึกษาพฤติกรรมการท่องเที่ยวของ นักท่องเที่ยวชาวตะวันออกกลางในประเทศไทย 2) เพื่อศึกษาพฤติกรรมการเลือกที่พักของนักท่องเที่ยว ชาวตะวันออกกลางในเขตกรุงเทพมหานคร 3) เพื่อศึกษาปัจจัยส่วนประสมทางการตลาดที ่มีผลต่อ การตัดสินใจเลือกที ่พักของนักท ่องเที ่ยวชาวตะวันออกกลางในเขตกรุงเทพมหานคร กลุ ่ม ตัวอย่างที่ใช้ในการวิจัย ได้แก่ นักท่องเที่ยวชาวตะวันออกกลางที่เดินทางเข้ามาใช้บริการที่พัก ในเขตกรุงเทพมหานคร จ านวน 400 คน ใช้แบบสอบถามเป็นเครื่องมือ ผลการวิจัยพบว่า นักท่องเที่ยวชาวตะวันออกกลางส่วนใหญ่เป็นเพศชาย มีรายได้ เฉลี่ยเดือนละ 5001 ดอลลาร์สหรัฐขึ้นไป มีภูมิล าเนามาจากประเทศสหรัฐอาหรับเอมิเรตส์ เดินท างม าพักในเขตก รุงเทพมห านค รเฉลี ่ยปีล ะ 2 ค รั้ง โดยแต ่ล ะค รั้งจะเข้าพักเป็น ระยะเวลา 2-7 วันโดยเฉลี ่ย เดินทางมาท่องเที ่ยวเป็นครอบครัว เลือกที ่พักเป็นโรงแรม ระดับ 4 ดาว ส ่วนใหญ ่เลือกที ่พักจากค าบอกเล่าของเพื ่อนหรือญาติ การเดินทางเข้ามา ท ่องเที ่ยวในป ระเทศไทยของนักท ่องเที ่ยวช าวตะวันออกกล างเป็นกา รเดินท างม าเพื ่อ พักผ่อนในวันหยุด ส่วนปัจจัยส่วนประสมทางการตลาดที่มีผลต่อพฤติกรรมการเลือกที่พัก ของนักท่องเที่ยวชาวตะวันออกกลาง พบว่าปัจจัยด้านผลิตภัณฑ์ ปัจจัยด้านราคา ปัจจัยด้านช่องทางการจัด จ าหน่าย ปัจจัยด้านบุคคล ปัจจัยด้านลักษณะทางกายภาพและปัจจัยด้านกระบวนการมีผลต่อพฤติกรรม การเลือกที่พักอยู่ในระดับมาก และพบว่าปัจจัยด้านการส่งเสริมการตลาด มีผลอยู่ในระดับปานกลาง The objectives of this study are to: 1) To study the travel behavior of tourists from the Middle East in Thailand 2) To study the services behavior of tourists from the Middle East in Bangkok. 3) To study the factors that affects the decision of the Middle East to choose the accommodation in Bangkok. This research is quantitative research. The samples used in this study were 400 Middle East tourists traveling to Bangkok and finding the accommodation. A tool used to collect data was questionnaire and analyzed by using frequency, percentage, mean and standard deviation. Test hypothesis by using Chi-square. The results showed that the Middle East were mostly males than females. They travel to stay in Bangkok at an annual average of 2 times, each time for a period of 2-7 days. They tend to travel as a family, stayed in a 4-star hotel. Mostly of United of Arab Emirate and Kuwait tourist travelling objective is for a holiday, and mostly of Oman tourist to seek medical / health check, this data was detailed from hearsay of friends / relatives. Marketing factors affecting the decision choice of the Middle East is relatively high, with an average of 4.19. The People factor is at a high level with an average of 4.13, Products at a high level with an average of 3.93, the distribution channel (Place) with an average of 3.93, and Physical at a high level with an average of 3.67, Price with the average level in the 3.54, and lastly Promotion is moderate, with an average of 2.95.